Effect of leg action on stroke perfiormance in swimming - Keskinen, K. L.; Komi, P. V. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The present study was designed to make comparisons among biomechanical parameters between normal crawl (CN) and crawl arm swimming (CA). These parameters included mean velocity (V), stroke rate (SR) and distance per stroke (d/S). The comparisons were complemented with the simultaneous recording of blood lactate (BLa) responses. Eight well conditioned competitive male swimmers carried out two sets of 15 times 100 m swims in both ways. In the comparisons of BLa vs V diagrams, CN and CA demonstrated different (P < 0.05) V values at 0.5 mM increase in BLa (anaerobic threshold, AT). The d/S was longest around aerobic-anaerobic transition. The values of d/S were higher (P < 0.05) in the CN curve when BLa increased by 0.5 mM above basal level and at V above AT. In CA swimming the SR curve became different (P < 0.05) from that of the CN at higher levels of V and BLa. However, at maximum pace SR values were equally high (0.76 Hz) in both swimming conditions. It is concluded that the support of leg kick could be seen in d/S values at V around AT and above, as well as in SR values at higher intensity levels.